Gestural Interface to Support Car Drivers Interacting with Smartphone: A Systematic Literature Review - Ganasan, J. (Springer Science and Business Media Deutschland GmbH, 2020)
With the rise in car-crash cases coupled with driversâ negligence has led to numerous deaths and injuries in todayâs transportation system. This catastrophic incidents are mainly attributed to the constant use of smartphone-user-interfaces while driving cars; especially in a confined space that requires minimal distraction. Since it is difficult to prevent drivers from constantly interacting with smartphones, many solutions have been developed to minimize driverâs distractions while interacting with smartphones. For instance, in-vehicle information systems (IVIS), Head-up and Google Glass are mainly for modern cars and has adopted voice recognition, which averagely achieve their targets. Voice recognition suffers from unattended sound and bad weather, hence touch-less and mid-air were introduced using gestural interface, yet a proper ambience was required. Thus, a further investigation is needed to critically explore the capabilities of gestural interface and how they support driverâs interaction. Consequently, the main objective of this study is to explore the existing gestures used to interact with smartphones are able to support driversâ interactions as they drive in a confined space with limited distraction. To achieve this, databases from various electronic platforms were studied and identified with the matched major terms or keywords related to gestural interfaces to draw a systematic literature review paper. The study produce significant results on existing gestures and car crash cases. One major findings was the invention of Google Glass which is in line with technology today, yet statistics of car crash cases does not seemingly reduce. In conclusion, various potential gestural interaction were identified to overcome certain issues with the existing gestures and support driversâ interaction while driving. In general however, it was perceived that existing gestures have limitations or do not entirely support driversâ interactions while driving. Â© 2020, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.